2021
DOI: 10.1101/2021.05.11.443659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Variant Identification Using a Genome Tiling Array and Genotyping Probes

Abstract: With over three million deaths worldwide attributed to the respiratory disease COVID-19 caused by the novel coronavirus SARS-CoV-2, it is essential that continued efforts be made to track the evolution and spread of the virus globally. We previously presented a rapid and cost-effective method to sequence the entire SARS-CoV-2 genome with 95% coverage and 99.9% accuracy. This method is advantageous for identifying and tracking variants in the SARS-CoV-2 genome when compared to traditional short read sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The tiling array is identical to the previously described DNA chip design (Centrillion Technologies) 11,13,14 . Nucleic acid extraction was performed using the Magnetic Bead 96 Viral Isolation Kit (Bioperfectus Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The tiling array is identical to the previously described DNA chip design (Centrillion Technologies) 11,13,14 . Nucleic acid extraction was performed using the Magnetic Bead 96 Viral Isolation Kit (Bioperfectus Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Using the total number of high‐quality calls as the reference call count, the number of true variant calls identified correctly, and the number of incorrect identified calls, accuracy calculations are performed. Coverage is calculated by the total number of calls (reference base or variant calls) divided by the size of the SARS‐CoV‐2 reference genome 23 . Sequence alignment was performed using Geneious Software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognizing the limitations to throughput for the BBP-RMAv.2 suggests that using it as a supplemental test for many different screening tests may be its initial role. Modifications to the platform can increase throughput and reduce cost (Shimada et al, 2021), such that the primers and tiles that were demonstrated effective here could be more practically applied.…”
Section: Discussionmentioning
confidence: 99%